The effect of internship experience, motivation, and job interest on job readiness among Muslim university students: Campus atmosphere as an intervening - Septiana, Ria; Atika, Atika; Harahap, Muhammad Ikhsan (LPMP Imperium, 2024)
This study investigates the effects of internship experience, motivation, and job interest on work readiness, with the campus atmosphere serving as an intervening variable among students at the Islamic University of North Sumatra. The sample consisted of 100 participants, and data were collected through questionnaires—the analysis employed regression techniques to evaluate the relationships among the variables. The findings reveal that internship experience positively influences the campus atmosphere. At the same time, motivation does not show a significant effect. Additionally, job interest positively impacts the campus atmosphere. All three factors—internship experience, motivation, and job interest—positively affect work readiness. However, the campus atmosphere does not significantly influence work readiness. The analysis results show that the campus atmosphere does not influence how internship experience affects work readiness. It also does not affect how motivation and job interest relate to work readiness.